Preparation method of nano zirconium oxide powder

By controlling the concentration ratio and pH of zirconium chlorine and oxalic acid in the sol-gel method, combined with spray drying and sand grinding technology, nanozirconium oxide powder was prepared, which solved the agglomeration and agglomeration problems and achieved uniform particle size and high purity nanozirconia powder production.

CN119320165APending Publication Date: 2025-01-17XIANDAO THIN FILM MATERIALS GUANGDONG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411291580.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

When preparing nanozirconia powders with the existing sol-gel method, the precursor is too hard to break when drying, resulting in serious agglomeration and agglomeration, which is difficult to meet the requirements of uniform particle size distribution and purity of nano-scale powders.

Method used

Using zirconium oxychloride as raw material and adding oxalic acid as flocculant, nanozirconium oxide powder is prepared by stirring, washing, spray drying, calcining, sanding and secondary spray drying steps, and the concentration ratio of zirconium oxychloride octahydrate and oxalic acid is controlled to 1:5~7, adjust the pH to 7~9, and use double tank circulating sand grinding to fine particle size.

Benefits of technology

The problem of excessive hardness of the precursor is not easy to break. The prepared nanozirconia powder is uniform in particle size, agglomeration phenomenon is reduced, and the purity is high, which meets the requirements of nanozirconia powders in various fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320165A_ABST
    Figure CN119320165A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of superfine powder preparation, and discloses a preparation method of nano zirconium oxide powder. The preparation method comprises the following steps: adding an oxalic acid solution into a zirconium oxychloride solution under a stirring condition to obtain sol; aging the obtained sol, and adding ammonia water to adjust the pH value to 7-9 to obtain gel; washing the obtained gel, and performing spray drying to obtain precursor powder; then carrying out calcination treatment at the temperature of 800-900 DEG C to obtain calcined powder; mixing the obtained calcined powder with water, and grinding to obtain slurry; and carrying out secondary spray drying on the obtained slurry to obtain the nano zirconium oxide powder. According to the preparation method, zirconium oxychloride is used as a raw material, oxalic acid is added as a complexing agent, ammonia water is used for adjusting the pH value to obtain a precursor, and the nano zirconium oxide powder is obtained through washing, spray drying, calcining, grinding and secondary spray drying. The preparation method is simple, and the obtained product has the advantages of small particle size, uniform distribution and difficulty in agglomeration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ultrafine powder preparation, and specifically relates to a method for preparing nano zirconium oxide powder. Background Art

[0002] Zirconia (ZrO2) is a metal oxide material that is resistant to high temperatures (melting point up to 2680°C), corrosion-resistant, and has high hardness (Mohs hardness of 8.5). It not only has excellent physical properties, such as high strength, high hardness, good thermal shock resistance, wear resistance, and low thermal conductivity (thermal conductivity is 2.09W / mol·K), but also has stable chemical properties, good acid and alkali corrosion resistance in oxidizing or reducing atmospheres, and even exhibits good biocompatibility. It plays a vital role in electronic products, ceramics, catalysis, and special refractory materials.

[0003] At present, the main methods for preparing nano-zirconia include coprecipitation, hydrothermal method, sol-gel method, etc. Among them, the powder prepared by the coprecipitation method has poor dispersibility and low sintering activity, and the hydrothermal method has complex equipment, high cost, high energy consumption, and long time consumption, which is not easy to be applied in large-scale industrialization. However, the sol-gel method has low raw material prices, low requirements for equipment, low cost, low energy consumption, and is easier to mass produce. Therefore, zirconium oxychloride is generally used as raw material to produce zirconium oxide powder by sol-gel method.

[0004] Invention patent CN102743979A adds dispersant and precipitant oxalic acid (ammonium oxalate) to prepare zirconium oxalate sol precursor, and obtains nano zirconium oxide powder after drying and calcination; invention patent CN103938133A uses zirconium oxychloride as raw material, adds ammonia water or oxalic acid to obtain precursor, and obtains nano zirconium oxide powder after drying and calcination; invention patent CN102743978B uses zirconium oxychloride, yttrium salt, and oxalic acid (ammonium oxalate) as raw materials, adds dispersant and reacts for a period of time, adds ammonia water to adjust the pH to 4-9, and then calcines to synthesize yttrium-doped zirconium oxide. Since zirconium oxalate sol will agglomerate when directly dried and is hard and not easy to break, the zirconium oxide powder calcined later will have serious agglomeration and agglomeration, which is not easy to meet the requirements for nano zirconium oxide powder in various fields. Summary of the invention

[0005] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing nano zirconium oxide powder. The preparation method of the present invention uses zirconium oxychloride as a raw material, adds oxalic acid as a flocculant and ammonia water to adjust the pH to obtain a precursor, and obtains nano zirconium oxide powder by washing, spray drying, calcination, sand milling, and secondary spray drying. The method of the present invention solves the problem that the precursor in the sol-gel method is too hard to break during drying. At the same time, the synthesized zirconium oxide powder can reach the nanometer level, with uniform particle size distribution and no obvious agglomeration phenomenon, which can meet the requirements of nano zirconium oxide in various fields.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing nano zirconium oxide powder comprises the following preparation steps:

[0008] (1) adding an oxalic acid solution to a zirconium oxychloride solution under stirring to obtain a sol; aging the obtained sol and then adding ammonia water to adjust the pH to 7 to 9 to obtain a gel;

[0009] (2) washing the gel obtained in step (1) and spray drying it to obtain a precursor powder; and then calcining it at a temperature of 800 to 900° C. to obtain a calcined powder;

[0010] (3) mixing the calcined powder obtained in step (2) with water and grinding the mixture to obtain a slurry; and spray-drying the obtained slurry for a second time to obtain nano zirconium oxide powder.

[0011] Furthermore, the stirring speed in step (1) is 100 to 200 rpm.

[0012] Furthermore, in step (1), the concentration of the oxalic acid solution is 1.75 to 3.5 mol / L; the concentration of the zirconium oxychloride solution is 0.35 to 0.5 mol / L. More preferably, the ratio of the concentration of the zirconium oxychloride solution to the concentration of the oxalic acid solution is 1:5 to 7.

[0013] Furthermore, the aging treatment time in step (1) is 0.5 to 1 h.

[0014] Furthermore, the washing in step (2) refers to washing with pure water until the conductivity is less than 500us / cm.

[0015] Furthermore, the rotation speed of the spray drying in step (2) is 20000-30000 rpm.

[0016] Furthermore, the calcination treatment time in step (2) is 4 to 6 hours.

[0017] Furthermore, the grinding treatment in step (3) refers to sand grinding treatment using a double-tank circulating sand mill.

[0018] Furthermore, the rotation speed of the secondary spray drying in step (3) is 20000-30000 rpm.

[0019] The preparation method of the present invention relates to the following reaction equation:

[0020] ZrOCl2·8H2O+H2C2O4·2H2O→ZrOC2O4+2HCl+10H2O;

[0021] NH3·H2O+HCl→NH4Cl+H2O;

[0022] 2ZrOC2O4+O2→2ZrO2+4CO2.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention controls the concentration ratio of zirconium oxychloride octahydrate to oxalic acid to be 1:5 to 7. The zirconium oxide powder particles prepared under this concentration ratio have a moderate particle size, a uniform size distribution, and no obvious agglomeration phenomenon, and the product purity is high.

[0025] (2) In the present invention, ammonia water is added to adjust the pH of the solution to 7-9, neutralize the HCl content in the sol, and reduce corrosion to the equipment.

[0026] (3) The present invention adopts spray drying to carry out drying, reduces powder agglomeration by high rotation speed, and solves the problem that the precursor is too hard to be broken during drying.

[0027] (4) The present invention further adopts a double-tank circulating sand milling method to refine the particle size, which can reduce the particle size of the zirconium oxide powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The present invention is a process flow chart of a method for preparing nano zirconium oxide powder in an embodiment of the present invention.

[0029] Figures 2 to 4 They are SEM images of the nano zirconium oxide powders obtained in Examples 1 to 3 respectively. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0031] Example 1

[0032] A method for preparing nano zirconium oxide powder, the process flow chart is as follows Figure 1As shown, the preparation steps include:

[0033] (1) Weighing 1127.9 g of zirconium oxychloride octahydrate, and preparing it into a 0.35 mol / L zirconium oxychloride solution A; weighing 448 g of oxalic acid, and preparing it into a 1.75 mol / L oxalic acid solution B; adding solution B to solution A at a rate of 180 mL / min, stirring was started during the whole process, and the speed was controlled at 150 rpm to obtain sol C; after aging sol C for 0.5 h, analytical pure ammonia was added to adjust the solution pH to 7, and gel D was obtained.

[0034] (2) Washing gel D with pure water until the conductivity of the supernatant is <500 us / cm, obtaining gel E; spray drying gel E once at a rotation speed of 23000 rpm to obtain powder F; calcining powder F in a tubular furnace at a calcination temperature of 800°C for 6 hours to obtain powder G.

[0035] (3) Powder G was mixed with water and then subjected to double-tank circulation sand milling for 20 times to obtain slurry H; slurry H was spray dried for a second time at a rotation speed of 23,000 rpm to obtain nano-scale zirconium oxide powder.

[0036] The SEM image of the zirconium oxide powder obtained in this example is as follows Figure 2 The particle size and purity (impurity content) test results are shown in Table 1.

[0037] Example 2

[0038] A method for preparing nano zirconium oxide powder, the process flow chart is as follows Figure 1 As shown, the preparation steps include:

[0039] (1) Weighing 1127.9 g of zirconium oxychloride octahydrate, and preparing it into a 0.4 mol / L zirconium oxychloride solution A; weighing 448 g of oxalic acid, and preparing it into a 2.4 mol / L oxalic acid solution B; adding solution B to solution A at a rate of 190 mL / min, stirring was started during the whole process, and the speed was controlled at 150 rpm to obtain sol C; after aging sol C for 0.75 h, analytical pure ammonia was added to adjust the solution pH to 8, and gel D was obtained.

[0040] (2) Wash gel D with pure water until the conductivity of the supernatant is <500 us / cm to obtain gel E; spray dry gel E once at a rotation speed of 25,000 rpm to obtain powder F; calcine powder F in a tubular furnace at a calcination temperature of 850°C for 5 hours to obtain powder G.

[0041] (3) Powder G was mixed with water and then subjected to double-tank circulation sand milling for 20 times to obtain slurry H; slurry H was spray dried for a second time at a rotation speed of 25,000 rpm to obtain nano-scale zirconium oxide powder.

[0042] The SEM image of the zirconium oxide powder obtained in this example is as follows Figure 3 The particle size and purity (impurity content) test results are shown in Table 1.

[0043] Example 3

[0044] A method for preparing nano zirconium oxide powder, the process flow chart is as follows Figure 1 As shown, the preparation steps include:

[0045] (1) Weighing 1127.9 g of zirconium oxychloride octahydrate, and preparing it into a 0.5 mol / L zirconium oxychloride solution A; weighing 448 g of oxalic acid, and preparing it into a 3.5 mol / L oxalic acid solution B; adding solution B to solution A at a rate of 200 mL / min, stirring was started during the whole process, and the speed was controlled at 150 rpm to obtain sol C; after aging sol C for 1 hour, analytical pure ammonia was added to adjust the solution pH to 9, and gel D was obtained.

[0046] (2) Wash gel D with pure water until the conductivity of the supernatant is <500 us / cm to obtain gel E; spray dry gel E once at a rotation speed of 30,000 rpm to obtain powder F; calcine powder F in a tubular furnace at a calcination temperature of 900°C for 4 hours to obtain powder G.

[0047] (3) Powder G was mixed with water and then subjected to double-tank circular sand milling for 20 times to obtain slurry H; slurry H was spray dried for a second time at a rotation speed of 30,000 rpm to obtain nano-scale zirconium oxide powder.

[0048] The SEM image of the zirconium oxide powder obtained in this example is as follows Figure 4 The particle size and purity (impurity content) test results are shown in Table 1.

[0049] Comparative Example 1

[0050] In the preparation method of a nano zirconium oxide powder of this comparative example, compared with Example 1, the concentration of oxalic acid solution B is reduced to 1.5 mol / L, and the rest is the same.

[0051] The zirconium oxide powder obtained in this comparative example has serious agglomeration phenomenon, and the test results of its particle size and purity (impurity content) are shown in Table 1.

[0052] Comparative Example 2

[0053] In the preparation method of a nano zirconium oxide powder of this comparative example, compared with Example 3, the concentration of the oxalic acid solution B is increased to 4.0 mol / L, and the rest is the same.

[0054] The zirconium oxide powder obtained in this comparative example has serious agglomeration phenomenon, and the test results of its particle size and purity (impurity content) are shown in Table 1.

[0055] Table 1. Zirconia powder particle size and purity test results

[0056]

[0057]

[0058] It can be seen from the comparison results of Comparative Example 1 and the embodiment in Table 1 that when the concentration ratio of oxalic acid is lower than 1:5, the particle size of the prepared zirconium oxide powder particles is larger, the size distribution is uneven, and the agglomeration phenomenon is serious, and the purity of the product is reduced. The reasons are: 1) The oxalic acid concentration is low, the zirconium ion complexation is insufficient, and the uncomplexed zirconium ions are prone to aggregation and hydrolysis reactions, forming larger zirconium oxide precursor crystal nuclei, resulting in an increase in the particle size of the zirconium oxide particles generated during the drying and calcining process; 2) The oxalic acid concentration is low, the particle growth cannot be effectively controlled, the particle size uniformity is poor, the zirconium ions cannot be fully complexed, and the generated precursor particles are more likely to agglomerate, thereby generating large pieces of zirconium oxide particles in the subsequent calcination process; 3) The oxalic acid concentration is low, the zirconium ion complexation is incomplete, which will lead to the generation of by-products and the formation of impurities, which reduces the purity.

[0059] By comparing the results of comparative example 2 with the embodiment, it can be seen that when the concentration ratio of oxalic acid is higher than 1:7, the particle size of the prepared zirconium oxide powder particles is too small, the size distribution is uneven, and the agglomeration phenomenon is serious, and the purity of the product is reduced. The reasons are: 1) excessive oxalic acid concentration will inhibit the growth of the zirconium oxide precursor crystal nucleus, resulting in too small particle size; 2) excessive oxalic acid concentration, too small particle size, and its high particle surface energy make the particles easy to agglomerate together; 3) excessive oxalic acid concentration, too many by-products are generated during the calcination process and remain in the zirconium oxide powder, reducing its purity.

[0060] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing nano zirconium oxide powder, characterized in that: The method comprises the following preparation steps: (1) adding an oxalic acid solution to a zirconium oxychloride solution under stirring to obtain a sol; aging the obtained sol and then adding ammonia water to adjust the pH to 7 to 9 to obtain a gel; (2) washing the gel obtained in step (1) and spray drying it to obtain a precursor powder; and then calcining it at a temperature of 800 to 900° C. to obtain a calcined powder; (3) mixing the calcined powder obtained in step (2) with water and grinding the mixture to obtain a slurry; and spray-drying the obtained slurry for a second time to obtain nano zirconium oxide powder.

2. The method for preparing nano zirconium oxide powder according to claim 1, characterized in that: The stirring speed in step (1) is 100-200 rpm.

3. The method for preparing nano zirconium oxide powder according to claim 1, characterized in that: The concentration of the oxalic acid solution in step (1) is 1.75-3.5 mol / L; the concentration of the zirconium oxychloride solution is 0.35-0.5 mol / L.

4. The method for preparing nano zirconium oxide powder according to claim 3, characterized in that: The concentration ratio of the zirconium oxychloride solution to the oxalic acid solution is 1:5-7.

5. The method for preparing nano zirconium oxide powder according to claim 1, characterized in that: The aging treatment time in step (1) is 0.5 to 1 h.

6. The method for preparing nano zirconium oxide powder according to claim 1, characterized in that: The washing in step (2) refers to washing with pure water until the conductivity is less than 500us / cm.

7. The method for preparing nano zirconium oxide powder according to claim 1, characterized in that: The rotation speed of the spray drying in step (2) is 20000-30000 rpm.

8. The method for preparing nano zirconium oxide powder according to claim 1, characterized in that: The calcination time in step (2) is 4 to 6 hours.

9. The method for preparing nano zirconium oxide powder according to claim 1, characterized in that: The grinding process in step (3) refers to sand grinding process using a double-tank circulating sand mill.

10. The method for preparing nano zirconium oxide powder according to claim 1, characterized in that: The rotation speed of the secondary spray drying in step (3) is 20000-30000 rpm.

Citation Information

Patent Citations

  • Method for preparing modified zirconia ceramic ultrafiltration membrane via yttrium doping

    CN102743978B

  • Preparation method of zirconia ceramic ultrafiltration film

    CN102743979A

  • Polycrystalline diamond taking zirconia fiber as toughening phase and preparation method thereof

    CN103938133A